2012
DOI: 10.4038/tar.v23i4.4864
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Performance of Purple Nutsedge (<i>Cyperus rotundus</i> L.) and Onion (<i>Allium cepa</i> L.) as Affected by Different Sources of Nitrogen

Abstract: ABSTRACT. Experiments were conducted in Yala 2010 and Maha 2010/11

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Such a superior reproduction ability makes this species invasive and harmful, especially in upland agricultural production systems. Reports have indicated that CR can cause a 35-89% reduction in the yields of cabbage, tomato, cucumber, green bean, carrot, okra, bell pepper, onion, garlic and many other crops [6][7][8][9]. According to a study by Bendixen and Nandihalli [2], CR is disseminated in over 92 tropical and subtropical countries around the world and causes harvest losses in more than 50 crops.…”
Section: Introductionmentioning
confidence: 99%
“…Such a superior reproduction ability makes this species invasive and harmful, especially in upland agricultural production systems. Reports have indicated that CR can cause a 35-89% reduction in the yields of cabbage, tomato, cucumber, green bean, carrot, okra, bell pepper, onion, garlic and many other crops [6][7][8][9]. According to a study by Bendixen and Nandihalli [2], CR is disseminated in over 92 tropical and subtropical countries around the world and causes harvest losses in more than 50 crops.…”
Section: Introductionmentioning
confidence: 99%